Five total strangers - Richards, Natalie D. (Naperville, IL : Sourcebooks Fire, 2020)
Desperate to reach her grieving mother, Mira joins a group of college students driving home after their flight is stranded, but the road conditions are not the only mortal danger they face--
Ages 14-18.
Grades 10-12.
HL610L
Decoding demand: 95 (very high) Semantic demand: 100 (very high) Syntactic demand: 86 (very high) Structure demand: 88 (very high)
Keywords: Blizzards -- Juvenile fiction; Automobile travel -- Juvenile fiction; Stalking -- Juvenile fiction; Secrecy -- Juvenile fiction; Young adult fiction; Horror fiction; Thrillers (Fiction)